INCIDENCE AND FACTORS RELATED TO THE APPEARANCE OF PRESSURE INJURIES IN AN INTENSIVE CARE UNIT (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objectives: identify the incidence and characterize pressure injuries in an adult intensive care unit regarding the occurrence, locations and risk factors, and verify whether there is an association between these and the appearance of the injuries. Method: observational, cohort, prospective study, developed in an intensive care unit of a tertiary hospital, from October to December 2019. The population consists of adults on the first day of admission to the unit, without pressure injury at admission. Participants were monitored during hospitalization, sociodemographic and clinical variables, and risk assessment of developing a pressure injury, skin assessment and Braden scale were collected daily. Pearson’s chi-square tests and student’s t-test were used to assessing the relationship between variables and injuries. For the analyzes, a significance level (α) of 5% was considered. Results: 40 participants were included, 20% had pressure injuries with a predominance of stages 1 and 2; the main affected sites were the sacral region followed by the calcaneus. The average hospital stay was 23.38 days for the injured group and 5.77 days for the non-injured group; time showed a significant relationship with the appearance of lesions (p = 0.002). Conclusion: it was concluded that the most affected site was the sacral region and grade 1 was the most frequent staging; length of stay was the variable that influenced the appearance of injuries.